1993
DOI: 10.1093/jnci/85.10.801
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Erythropoietin Therapy for Anemic Cancer Patients on Combination Chemotherapy

Abstract: We conclude that rHuEPO is safe and effective for reversing anemia related to advanced cancer or to chemotherapy for cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
68
0
3

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(80 citation statements)
references
References 0 publications
9
68
0
3
Order By: Relevance
“…Furthermore, epoetin b was well tolerated and was significantly superior to standard care in increasing Hb concentrations, irrespective of the type of tumour, or the presence and nature of chemotherapy. The findings are consistent with those reported in other clinical studies of epoetin (Case et al, 1993;Cascinu et al, 1994;Henry and Abels, 1994;Dammacco et al, 1998;Nowrousian, 1998;ten Bokkel Huinink et al, 1998;Ludwig, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, epoetin b was well tolerated and was significantly superior to standard care in increasing Hb concentrations, irrespective of the type of tumour, or the presence and nature of chemotherapy. The findings are consistent with those reported in other clinical studies of epoetin (Case et al, 1993;Cascinu et al, 1994;Henry and Abels, 1994;Dammacco et al, 1998;Nowrousian, 1998;ten Bokkel Huinink et al, 1998;Ludwig, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…However, Lavey and Dempsey (1993) used 300 U kg-' three times only during the first week and then 150 U kg-' (three times a week) for the remainder of the RT. This dosing schedule is fairly close to that used in the two largest experiences of r-HuEPO in patients with cancer-related anaemia (Abels, 1992a(Abels, ,b, 1993Ludwig et al, 1993Ludwig et al, , 1994 including patients receiving combination chemotherapy (Case et al, 1993). Response rates in these studies are defined differently but are approximately in the 40 to 50% range of patients tested, which is similar to our results.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, this trend toward improved QOL in r-HuEPO-treated patients is reflected in the literature with most (Abels, 1992b(Abels, , 1993Case et al, 1993;Ludwig et al, 1993;Leitgeh et al, 1994) but not all (Dusenberg et al, 1994) series showing a benefit in various quality of life parameters over concurrent or historical controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies, both placebo-controlled and open-label, have consistently shown that increasing haemoglobin values has a measurable and significant effect on QOL parameters in cancer patients whether they are receiving (Abels, 1993;Case et al, 1993;Henry and Abels, 1994;Leitgeb et al, 1994;Glaspy et al, 1997;Demetri et al, 1998) or not receiving concurrent chemotherapy (Ludwig et al, 1995). In all of these studies, haemoglobin was increased by the administration of recombinant human erythropoietin (rHuEPO, epoetin alfa).…”
Section: Improved Quality Of Lifementioning
confidence: 99%